Reversing Frailty in Older Adults: A Scoping Review - Fonka, Aurelie Tonjock (Université d'Ottawa / University of Ottawa, 2022)
Background: The exponential growth of the aging population makes research on reversing frailty increasingly important. Objective: To explore the concept of reversing frailty in older adults and identify existing interventions that achieve frailty reversal as an outcome. Methods: We used a five-stage scoping review methodology outlined by Arksey and O’Malley and enhanced by Joanna Briggs, Levac, and colleagues. We critically appraised all eligible studies and synthesized data using descriptive and narrative analyzes. We searched CINAHL, EMBASE, PubMed, and Web of Science. Results: The concept of reversing frailty seems complex, and no standard intervention exists.That notwithstanding, a few types of single- or multi-component intervention characteristics showed effectiveness in reversing frailty. Conclusion: Frailty can be reversed. However, concept analysis is needed to clarify and define reverse frailty. To ensure maximum effectiveness, the identified interventions, ranging from mostly physical activity to a combination of physical activity and nutrition, could be tailored to each individual’s needs.
Keywords: Reverse frailty; Frailty domains; Single component; Multi-component; Scoping review